Low Benthic Oxygen and High Internal Phosphorus-Loading are Strongly Associated With the Invasive Macrophyte Nitellopsis obtusa (starry stonewort) in a Large, Polymictic Lake - Harrow-Lyle, Tyler J.; Kirkwood, Andrea E. (Frontiers in Environmental Science, 2021)
Lake Scugog is an important headwater to the Trent Severn-Waterway in Ontario, Canada, and known for its prized sport fishery. In recent years, notable ecosystem-level changes have occuredoccurred coinciding with the emergence of the non-native invasive charophyte Nitellopsis obtusa. Despite N. obtusa arriving in North America in the early 1970s, studies documenting the impact of N. obtusa on invaded ecosystems are scarce. Given the increasing dominance of N. obtusa in inland waters of the Great Lakes basin, we investigated the ecosystem-level impacts of N. obtusa in Lake Scugog over a 3-year period. We show for the first time a strong association between N. obtusa occurrence and biomass with benthic anoxia in this shallow, polymictic lake. We found Bbenthic dissolved oxygen concentrations were significantly lower (p-value < 0.001) at sites with N. obtusa compared to sites without N. obtusa. Additionally, We also found that N. obtusa biomass was a negative predictor of near-bed oxygen concentration (R2 = 0.59, p-value < 0.001). Knowing that anoxia can promote the internal loading of phosphorus, we measured soluble reactive phosphorus (SRP) in the pore-water of sediments at each site, and found N. obtusa biomass explained 90% of sediment pore-water SRP (R2 = 0.90, p-value < 0.001). These notable associations between N. obtusa and key lake elements indicates that N. obtusa may be acting as an ecosystem engineer in invaded lakes, by altering the biogeochemical fates of oxygen and phosphorus.